Prions The New Biology of Proteins - Soto, Claudio (CRC/Taylor & Francis, 2006)
"Prions: The New Biology of Proteins provides a well-organized overview of what is presently known about prion-related diseases. This comprehensive work reviews the clinical symptoms, epidemiology, and neuropathology of the disease. It focuses on evidence supporting the idea that TSEs result from an entirely novel disease mechanism, involving transmission by replication of the misfolding of a single protein in the absence of nucleic acids. Following this hypothesis, the book examines the structure, conversion, and mechanism of prion propagation and details its cellular biology. It explores the transmission of the disease, discusses the challenges involved with diagnosis, and considers the various therapeutic avenues that are presently being explored."--Jacket.